FROM SELF-AWARENESS TO COMMITMENT: STAGES OF RELIGIOUS TRANSFORMATION AMONG CHRISTIAN INMATES IN A CLASS IIA NARCOTICS PENITENTIARY - Situmorang, Anita Carolina (Politeknik Ilmu Pemasyarakatan, 2025)
Religion serves as a primary source of spiritual and moral guidance that enables individuals to cope with problems, reduce stress, and manage anxiety. Numerous studies have demonstrated that religiosity plays a significant role in fostering mental health and promoting more positive ways of dealing with life pressures. Incarcerated individuals constitute a population that experiences considerable emotional and psychological strain during their imprisonment. They frequently participate in religious development programs as a means of managing negative emotions through repentance and religious practice. This study aims to explore the experiential process of religious transformation among Christian inmates at the Jakarta Class IIA Narcotics Correctional Facility. Employing a qualitative approach, the research involved five informants who participated in in-depth and semi-structured interviews. The findings reveal that inmates’ transformation unfolds through several stages, including self-awareness, social support, motivation, and self-actualization, ultimately culminating in the development of personal commitment. Christian inmates who underwent religious guidance and experienced such transformation demonstrated greater consistency in practicing religious awareness. These findings provide strong evidence to recommend the enhancement of methods and strategies for Christian spiritual rehabilitation programs within the Jakarta Class IIA Narcotics Correctional Facility..